Information Boards as Forest Conservation Campaign in Bahorok Research Center, Langkat Regency, North Sumatera Utara, Indonesia - Berliani, Kaniwa; Elimasni; Jumilawaty, Erni; Nurtjahja, Kiki; Wahyuningsih, Hesti; Siregar, Etti Sartina; Nurwahyuni, Isnaini; Tanjung, Masitta; Priyani, Nunuk; Supriharti, Deny; Siregar, Julius Paolo (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Yayasan Ekosistem Lestari (YEL) in Bahorok Research Station in Bahorok Sub-district, Langkat District, is a very important location for this work. The hilly terrain of the area provides a beautiful landscape and varied flora and fauna with the main attraction being the corpse flower (Amorphophallus sp). With a preserved natural environment and unique ecological features, this research station allows other parties to participate in protecting the area in various conservation campaign, one of which is the installation/establishment of conservation information boards. Conservation information boards can raise public awareness about the importance of protecting forests and their natural environment. Information on ecosystems, flora, fauna, management, and the importance of conservation can be conveyed through these information boards. Information boards are widely used as an educational tool for local communities and visitors to the forest at the research station. They can learn about forest ecology, the negative impacts of deforestation, and sustainable ways of utilizing forest resources. They can learn about forest ecology, the negative impacts of deforestation, and sustainable ways of utilizing forest resources. Information boards can also be used to invite community participation in conservation efforts, which is expected to improve the quality of knowledge and understanding of conservation areas for communities, researchers, and tourists. Therefore, the installation/establishment of conservation information boards needs to be carried out at Bahorok Research Station, Batu Katak as one of the campaign and solutions to maintain the natural conditions in the forest and river.